3D-RISM-KH molecular theory of solvation and density functional theory investigation of the role of water in the aggregation of model asphaltenes - Da Costa, Leonardo M.; Hayaki, Seigo; Stoyanov, Stanislav R.; Gusarov, Sergey; Tan, Xiaoli; Gray, Murray R.; Stryker, Jeffrey M.; Tykwinski, Rik; Carneiro, J. Walkimar De M.; Sato, Hirofumi; Seidl, Peter R.; Kovalenko, Andriy (Physical Chemistry Chemical Physics, 2012)
We applied a multiscale modeling approach that involves the statistical-mechanical three-dimensional reference interaction site model with the Kovalenko-Hirata closure approximation (3D-RISM-KH molecular theory of solvation) as well as density functional theory (DFT) of electronic structure to study the role of water in aggregation of the asphaltene model compound 4,4′-bis(2-pyren-1-yl-ethyl)-2,2′-bipyridine (PBP) [X. Tan, H. Fenniri and M. R. Gray, Energy Fuels, 2008, 22, 715]. The solvation free energy and potential of mean force predicted by 3D-RISM-KH reveal favorable pathways for disaggregation of PBP dimers in pure versus water-saturated chloroform solvent. The water density distribution functions elucidate hydrogen bonding preferences and water bridge formation between PBP monomers. The ΔG values of -5 to -7 kcal mol for transfer of water molecules in chloroform to a state interacting with PBP molecules are in agreement with experimental results. Geometry optimization and thermochemistry analysis of PBP dimers with and without water bridges using WB97Xd/6-31G(d,p) predict that both PBP dimerization and dimer stabilization by water bridges are spontaneous (ΔG < 0). The H NMR chemical shifts of PBP monomers and dimers predicted using the gauge-independent atomic orbital method and polarizable continuum model for solvation in chloroform are in an excellent agreement with the experimental results for dilute and concentrated PBP solutions in chloroform, respectively [X. Tan, H. Fenniri and M. R. Gray, Energy Fuels, 2009, 23, 3687]. The DFT calculations of PBP dimers with explicit water show that bridges containing 1-3 water molecules lead to stabilization of PBP dimers. Additional water molecules form hydrogen bonds with these bridges and de-shield the PBP protons, negating the effect of water on the H NMR chemical shift of PBP, in agreement with experiment. The ΔG results show that hydrogen bonding to water and water-promoted polynuclear assembly bridging is as important as π-π interactions for asphaltene aggregation. © 2011 The Owner Societies.